Investigation of the relationship between lumbar spine MRI findings and pain in patients who received and did not receive Parkinson's treatment - Tuncer, Zeynep; Eren, Fatma Ayşen; Gürsoy Çirkinoğlu, Gözde; Beyaz, Serbülent Gökhan (The European Research Journal, 2023)
Objectives: Parkinson's disease is a chronic, progressive neurodegenerative disorder. Pain is a common symptom in Parkinson's disease, but the prevalence, characteristics, and documentation of its relationship with Parkinson's disease are insufficient. In this study, it was aimed to evaluate the relationship between lumbar spine magnetic resonance imaging (MRI) findings in patients who received and did not receive Parkinson's treatment. Methods: The demographic characteristics of patients with diagnosed Parkinson's disease were retrospectively obtained from the records. Their pain was grouped and the Hoehn Yahr stage at the first examination, and the interventional treatments performed were recorded. MRI measurements were made in the axial plane and sagittal plane of the spinal canal, whereas Ligamentum flavum measurements were made on both the right and left sides. Results: Twenty-six patients were included in the study. The average age was 73.5. Notably, 57.7% of patients were not diagnosed with Parkinson's disease prior to admission, while the Hoehn Yahr stage mostly comprised Stage 2 with 53.8%. Additionally, low back, waist, and hip pain was observed in 84.6% (n = 22), whereas 61.5% (n = 16) of patients experienced radicular pain. Epidural injections accounted for 33.2%. On lumbar MRI, the most narrow spinal segment on axial measurement was shown to be L4-L5. The axial spinal canal measurement of the Hoehn Yahr 1 group was observed to be significantly lower than the Hoehn Yahr 2 group. Conclusions: Optimal management for lumbar pain that increases with age is currently inadequate. There is a need to conduct larger studies on pain complaints, which is one of the frequently experienced non-motor symptoms in Parkinson's disease, as well as the interventional methods applied.